The youngest record of metriorhynchid crocodylomorphs, with implications for the extinction of Thalattosuchia. (September 2015) - Chiarenza, Alfio A.; Foffa, Davide; Young, Mark T.; Insacco, Gianni; Cau, Andrea; Carnevale, Giorgio; Catanzariti, Rita
Abstract: Here we describe an isolated tooth of a metriorhynchid crocodylomorph from the Hybla Formation (Aptian, Lower Cretaceous) of Rocca Chi Parra quarry (Montagna Grande, Calatafimi, Trapani Province), Sicily, Italy. The specimen shares with the Upper Jurassic taxon Plesiosuchus manselii a mediolaterally compressed conical tooth crown, noticeable lingual curvature, mesial and distal carinae with microscopic, rectangular contiguous denticles, strong distal curvature of the mesial margin, and the presence of weak 'carinal flanges' on the labial and lingual surfaces (which are preeminent at the mid-crown). This suite of morphologies is also present in an unnamed Valanginian (Lower Cretaceous) plesiosuchinan from France. However, the Sicilian tooth differs from these taxa in having more pronounced carinae, and faint apicobasally aligned enamel ridges. It also differs from P. manselii in having more extensive 'carinal flanges' on the labial surface. The specimen extends the known geological range of Metriorhynchidae and Thalattosuchia by approximately 7–8 million years. This overturns previous hypotheses of Metriorhynchidae becoming extinct early in the Early Cretaceous. Graphical abstract: Highlights: A tooth of a metriorhynchid crocodylomorph from the Aptian of Sicily is described. This specimen represents the most recent evidence of metriorhynchid crocodylomorphs. Such evidence falsifies Thalattosuchia extinction early in the Early Cretaceous.